2000
DOI: 10.1130/0016-7606(2000)112<1091:uhotca>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Uplift history of the Central and Northern Andes: A review

Abstract: The elevation of the Andean Cordillera is a crucial boundary condition for both climatic and tectonic studies. The Andes affect climate because they form the only barrier to atmospheric circulation in the Southern Hemisphere, and they intrigue geologists because they have the highest plateau on Earth formed at a noncollisional plate margin, the Altiplano-Puna. Yet, until recently, few quantitative studies of their uplift history existed. This study presents both (1) a review of the quantitative paleoelevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
405
3
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 977 publications
(471 citation statements)
references
References 97 publications
21
405
3
7
Order By: Relevance
“…The detailed pattern of elevational distributions and speciation is still there to be seen. Although uplift of the southern Andes was perhaps completed prior to the Tertiary, the northern Andes are not believed to have achieved heights above 1000 m until the Mid-Pliocene (Simpson 1979;Gregory-Wodzicki 2000). The Andean members of the floralis and nepos groups are thus probably no older than 4 or 5 million years.…”
Section: Discussion (A) Montane Speciationmentioning
confidence: 99%
“…The detailed pattern of elevational distributions and speciation is still there to be seen. Although uplift of the southern Andes was perhaps completed prior to the Tertiary, the northern Andes are not believed to have achieved heights above 1000 m until the Mid-Pliocene (Simpson 1979;Gregory-Wodzicki 2000). The Andean members of the floralis and nepos groups are thus probably no older than 4 or 5 million years.…”
Section: Discussion (A) Montane Speciationmentioning
confidence: 99%
“…Node numbers correspond to those in Fig. 6 of the northern Andes is unrealistic because the Andes are not a single entity; uplift did not happen instantaneously, and its timing probably varied latitudinally and longitudinally (Gregory-Wodzicki, 2000). The two splits could be as old as the Late Cretaceous, when the Andes were uplifted to elevations not greatly exceeding 1000 m (Simpson, 1979)-extant hoplocercine species occur mostly below 1000 m except for E. praestabilis, which has been found at elevations close to 2000 m (specimen 2156 in the Fundación Herpetológica Gustavo Orcés, Ecuador).…”
Section: Biogeography and Relative Divergence Timesmentioning
confidence: 99%
“…However, if this modest Late Cretaceous mountain chain did not represent a geographic barrier to the Enyalioides species living at that time, the splits must have occurred more recently when the northern Andes became high enough to be a barrier. The northern Andes, in particular the eastern Cordillera in Colombia, underwent rapid uplift 2-5 million years ago leading to a definitive separation between the Amazonian rain forest and the Chocó region (Van der Hammen et al, 1973;Simpson, 1979;Aleman and Ramos, 2000;Gregory-Wodzicki, 2000). Thus, ages of nodes 3 and 7 could be any time between the Late Cretaceous and the Pliocene; based on a rate of sequence evolution estimated for a group of agamid lizards The differences between divergence time estimates obtained using the uncorrelated lognormal method with and without partition-specific parameter estimates indicate that partitioning can have a significant impact on node height (age) estimates.…”
Section: Biogeography and Relative Divergence Timesmentioning
confidence: 99%
“…12.3) suggesting a minimum paleorelief of 1 800 m between the present plateau border and that basin by late Miocene time ). This assessment is also compatible with paleo-elevation estimates farther north based on leaf morphology by Gregory-Wodzicki (2000), who suggested that the Bolivian Altiplano had possibly reached about half of its present elevation by 10 Ma. New paleo-altimetry studies by Garzione et al (2006) using oxygen isotopes in paleosol carbonates in the Altiplano also indicate that the present elevation of the northern plateau region may had come into existence between 9 and 6 Ma.…”
Section: Tertiary Climate Characteristicssupporting
confidence: 75%